Peningkatan Kualitas Produksi Ikan Asap di Rumah Produksi Kampung Rawa Jaya Tobelo Melalui Inovasi Alat Pengasapan Ikan Sari Waruna - Indrayana, I Putu Tedy; Puni, M S; Manumpil, A; Huragana, Y M (Universitas Pendidikan Ganesha, 2020)
This community service aims to provide innovation in the fish smokehouse in Rawa Jaya Tobelo. The target of this activity is to be able to improve the quality of smoked fish production and packaging so that it has the potential to increase the selling value of the product. This activity was carried out for 5 months by implementing a collaborative strategy between the service team and the partner community. The focus of this service is (1) manufacturing